Dampak Dinamika Komunikasi di Media Sosial terhadap Pelestarian Lingkungan: Studi Kasus pada Kebijakan Penurunan Status Cagar Alam Kamojang dan Papandayan - Dandi Supriadi; Herlina Agustin (ULTIMA Comm, 2019)
Social media has transformed into a "free" advertising instrument. By using User-Generated Contents (UGC) technology, an instant publication about engaging activities in a particular area will encourage other people's interest to have the same experience. However, the effectiveness of tourism promotion turned out to have negative impacts, one of them is related to environmental issues because the behavior that has been published is not necessarily on the same track with the perspective of environmental conservation. It happened to Mount Kamojang and Papandayan nature reserve, West Java, where a part of the area has been converted into a nature tourism park. One reason for the change of status is to attract people's interest to visit the Kamojang and Papandayan areas. This interest could be seen from the many comments on social media that also promote the natural beauty of the place. By using a qualitative method with a case study approach, this study explains the dynamics involved in social media that influence the counter-productive behaviors in environmental issues. The results of the study show that social media contents have encouraged the public to access nature tourism areas, including the closed area in the Garut Regency. Additionally, the viral information was then used by stakeholders as a weapon to persuade the authorities to change the status of the area into a a tourist attraction. This study recommends a review of the policy related to the nature reserve's status amendment, considering the sustainability of environmental conservation in Indonesia. Keywords: kamojang papandayan, nature reserve, social media, UGC, promotion